2000
DOI: 10.1053/ejvs.2000.1171
|View full text |Cite
|
Sign up to set email alerts
|

Suprarenal Aortic Cross-Clamping in Elective Abdominal Aortic Aneurysm Surgery

Abstract: this data shows that suprarenal clamping, which is necessary for the radical treatment of juxtarenal aortic aneurysms, can be performed with a low risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 24 publications
0
42
0
1
Order By: Relevance
“…Giulini et al 20 compared suprarenal clamping for juxtarenal aneurysms and infrarenal clamping for regular AAA. Their perioperative mortality was 3.6% for the suprarenal group vs. 1.9% for the infrarenal one, which did not represent a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Giulini et al 20 compared suprarenal clamping for juxtarenal aneurysms and infrarenal clamping for regular AAA. Their perioperative mortality was 3.6% for the suprarenal group vs. 1.9% for the infrarenal one, which did not represent a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Between 0% and 40.5% of patients who undergo elective AAA repair suffer transient renal failure after suprarenal aortic cross-clamping. [1][2][3][4][5][6][13][14][15][16] Crawford et al reported that renal failure was the most common complication in their series of 101 juxta-and infrarenal AAAs, and the most common cause of early death, accounting for 63% (5/8) of deaths. 1 One of the major determinants of postoperative renal dysfunction is preexisting renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…It complicates both surgical repair of ruptured and nonruptured abdominal aortic aneurysms [2,3] and not only open repair of abdominal aortic aneurysms but also endovascular technique is associated with a significant degree of IR injury [4]. The overall incidence rate of ARF after vascular surgery has been reported to be 1.7 to 25% [5].…”
Section: Introductionmentioning
confidence: 99%